2008
DOI: 10.2320/matertrans.mra2008115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacancies on Deformation Behavior in Nanocrystalline Nickel

Abstract: The effects of vacancies on deformation of nanocrystalline Ni have been investigated by experiments and molecular dynamics (MD) simulations. In the experiments, nanocrystalline Ni specimens containing different numbers of vacancies were produced by electrodeposition and annealing, and their mechanical properties were investigated by tensile tests. As a result, the yield stress and fracture stress for the specimen containing more vacancies were lower than those for the one containing fewer vacancies. The MD sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The results consistently indicate lower yield points for the samples with higher concentration of vacancies. This corresponds to previous works which indicated that the presence of vacancies can decrease the yield point during any mechanical testing [21][22][23][24]. The observed difference in the initial stiffness (Figure 1, inset) is due to the different surface roughnesses.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The results consistently indicate lower yield points for the samples with higher concentration of vacancies. This corresponds to previous works which indicated that the presence of vacancies can decrease the yield point during any mechanical testing [21][22][23][24]. The observed difference in the initial stiffness (Figure 1, inset) is due to the different surface roughnesses.…”
Section: Resultssupporting
confidence: 87%
“…The effect of non-equilibrium vacancies on the mechanical response of metals is complex, ranging from strengthening effects due to Cottrell atmospheres, to dislocation motion impacted by climb and jog formation [20] and to weakening effects previously reported to impact dislocation nucleation [21][22][23][24]. Mukherjee et al [25] used two-dimensional models of nanoindentation tests and showed annihilation of vacancies in the compression zones and enlargement of vacancies in the tension zones under the indenter.…”
Section: Introductionmentioning
confidence: 98%
“…Point defects, which have a great impact on the mechanical properties and plastic deformation of nanocrystalline metals, have also been studied [14]. It was found that the yield stress and fracture stress for nanocrystalline Ni containing more vacancies were lower than those for the one containing fewer vacancies, and an increase in GB energy due to vacancies in the GB was suggested to enhance GB fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The creep mechanisms caused by intergranular dislocation slip (Weitzman creep), intergranular diffusion of vacancies (Nabarro-Herring creep)[35], and vacancy diffusion along the GB (Coble creep)[11] are all not consistent with the situation in this study. Studies have shown that GB deformations can be enhanced by vacancies in GBs because the creep rate for the vacancy-rich cell unit is more than twice that for the normal cell unit in the nanocrystalline NiW alloy[14]. The formation of deformation-induced vacancies at the GBs could be correlated with the Shockley partial dislocations and the initial vacancy concentration.…”
mentioning
confidence: 99%
“…Another important factor affecting the dislocation emission is the grain boundary characteristics such as defects, grain boundary segregation, and misorientation. However, there are only a few studies on the effects of the grain boundary characteristics on the mechanical properties of nanocrystalline metals [14,15].…”
Section: Introductionmentioning
confidence: 99%